Revisiting Indonesia's Zakat Law: Legal Analysis of Marine Product Zakat and Reform Proposals - Ahmad Muhasim; Moh. Asyiq Amrulloh; Abdullah Abdullah; Azman Ab. Rahman (Faculty of Sharia UIN Profesor Kiai Haji Saifuddin Zuhri Purwokero, 2026)
Indexed by Scopus